168k views
4 votes
The value of x for which the expressions 3x – 4 and 2x + 1 become

equal is
-3
0
5
1

User Danieln
by
4.4k points

2 Answers

3 votes

Answer:

5

Explanation:

1) make them equal to each other

2) put all the constants on one side and all the ones with x on the other

3) solve

User Johnathan Le
by
4.9k points
5 votes

Answer:


x=5

Explanation:

To determine for which value of x a pair of expressions will be equal, we will need to set them equal to each other and then solve for x.


3x-4=2x+1

First, we can add 4 to each side


3x=2x+5

Now we can subtract 2x from each side


x=5

Now, just to check our answer, we can plug in our answer back into the original equation to see whether we get the same result for each side


3(5)-4=2(5)+1\\\\15-4=10+1\\\\11=11

User Harish Gupta
by
5.5k points